Implementasi Tata Kelola dan Tanggung Jawab Sosial dalam Menunjang Kinerja Keuangan Saham Syariah Indonesia - Haryati, Tantina; Wilasittha, Acynthia Ayu; Putri, Sofie Yunida (Owner : Riset dan Jurnal Akuntansi, 2024)
The objective of this study is to examine the correlation between Islamic Corporate Governance (ICG) and Islamic Corporate Social Responsibility (ICSR) and the financial performance of companies that are listed on the Indonesian Sharia Stock Index (ISSI). The research data were collected from the annual financial reports of 250 companies that satisfied the requirement of being listed in the ISSI for five consecutive years and filing annual reports during that same period. An assessment was carried out on the financial statements to determine the utilization of eight ICG  and six ICSR indicators and to gauge economic performance by calculating Return on Assets (RoA) and Return on Equity (RoE). The results suggest that the adoption of ICG positively affects organizations' financial performance, whereas the adoption of ICSR does not substantially impact. These findings indicate that these companies' adoption of ICG and ICSR is limited despite their inclusion in the ISSI. These companies have not utilized many ICG  and ICSR  indicators. This study offers significant insights demonstrating that augmenting the use of ICG can improve firms' financial performance. However, there is a need to enhance awareness and implementation of ICSR. Furthermore, it emphasizes the significance of corporations prioritizing ICG  and ICSR  features as integral components of their comprehensive approach to enhancing their financial performance and social responsibility.